Empowering Oncology Nurses through Knowledge and Practice to Improve Transitions Following Treatment and Survivorship Care - Linda Watson; Christine Maheu; Sarah Champ; Margaret I Fitch (Elsevier, 2021)
Following cancer treatment, individuals can be left with physical, emotional, and practical consequences which influence their quality of life. Cancer survivors frequently require added knowledge and skills to handle the demands of everyday living after treatment. Oncology nurses are in an ideal position to address the needs of cancer survivors. This article describes an online interactive workshop for oncology nurses to introduce Canadian data on unmet needs of cancer survivors, highlight the contribution oncology nurses can make to survivorship care, and introduce a self-learning resource for survivor care. Didactic presentations and small group discussions were used and feedback from participants was positive. Online learning can be an effective approach for learning with international nursing colleagues and could be utilized for nurses with limited access to cancer nursing education.